Protein kinase‐dependent oxidative regulation of the cardiac Na+–K+ pump: evidence from in vivo and in vitro modulation of cell signalling. (17th May 2013) - Galougahi, Keyvan Karimi; Liu, Chia‐Chi; Garcia, Alvaro; Fry, Natasha A. S.; Hamilton, Elisha J.; Rasmussen, Helge H.; Figtree, Gemma A.
Key points The widely believed effects of β1 adrenergic receptors and protein kinase A (PKA) to stimulate the membrane Na+–K+ pump in cardiac myocytes are not easily reconciled with the effects of activation of the receptor and PKA on contractility in normal heart or with the benefit of β1 adrenergic blockade in heart failure. We show that reduction in PKA activity by β1 adrenergic blockade in vivo stimulates the Na+–K+ pump by reducing glutathionylation of one of its subunits, a reversible oxidative modification that inhibits pump activity. Na+–K+ pump stimulation induced by β1 adrenergic blockade in vivo is reversed by activation of PKA‐dependent signalling in isolated cardiac myocytes studied ex vivo. Inhibition of the myocyte Na+–K+ pump mediated by PKA‐ and redox‐dependent signalling pathways and downstream glutathionylation of a subunit of the Na+–K+ pump is readily reconciled with effects of PKA on contractility in normal heart and efficacy of β1 adrenergic blockade in heart failure. Abstract The widely reported stimulation of the cardiac Na+–K+ pump by protein kinase A (PKA) should oppose other effects of PKA to increase contractility of the normal heart. It should also reduce harmful raised myocyte Na+ levels in heart failure, yet blockade of the β1 adrenergic receptor (AR), coupled to PKA signalling, is beneficial. We treated rabbits with the β1 AR antagonist metoprolol to modulate PKA activity and studied cardiac myocytes ex vivo. Metoprolol increased electrogenic pump current (Ip) in voltage clamped myocytes and reduced glutathionylation of the β1 pump subunit, an oxidative modification causally related to pump inhibition. Activation of adenylyl cyclase with forskolin to enhance cAMP synthesis or inclusion of the catalytic subunit of PKA in patch pipette solutions abolished the increase in Ip in voltage clamped myocytes induced by treatment with metoprolol, supporting cAMP/PKA‐mediated pump inhibition. Metoprolol reduced myocardial PKA and protein kinase C (PKC) activities, reduced coimmunoprecipitation of cytosolic p47phox and membranous p22phox NADPH oxidase subunits and reduced myocardial O2−‐sensitive dihydroethidium fluorescence. Treatment also enhanced coimmunoprecipitation of the β1 pump subunit with glutaredoxin 1 that catalyses de‐glutathionylation. Since angiotensin II induces PKC‐dependent activation of NADPH oxidase, we examined the effects of angiotensin‐converting enzyme inhibition with captopril. This treatment had no effect on PKA activity but reduced the activity of PKC, reduced β1 subunit glutathionylation and increased Ip. The PKA‐induced Na+–K+ pump inhibition we report should act with other mechanisms that enhance contractility of the normal heart but accentuate the harmful effects of raised cytosolic Na+ in the failing heart. This scheme is consistent with the efficacy of β1 AR blockade in the treatment of heart failure.